Awareness and Preparedness of Fomite Transmission Among Malaysian Online Shoppers: A Cross-Sectional Survey - Abdul Hamid, Hisyam; Sarkam, Nor Aslily; Karuppanan, Mahmathi; Saleman, Abdul Rafeq; Husain, Noreen (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: COVID-19 outbreak is the greatest communicable disease that hit globally, caused by SARS-CoV-2 virus. Malaysia commenced a Movement Control Order (MCO) to contain the epidemic, and thereby altered consumer’s purchasing pattern drastically into online shopping, thus increase the demand of delivery services. The virus able to survive on surfaces up until 9 days depending on the type of surface. Nonetheless, the negligence of proper hygiene management among the vendor, the courier or the user can trigger fomite transmission. The aims of this study were to determine the level of awareness and readiness of fomite transmission caused by COVID-19 among Malaysian online shoppers by evaluating knowledge, precautionary measurements and psychological state. Methods: Convenience sampling method was used for data collection, and 416 respondents participated. The survey instrument comprised of 2 parts; socio-demographic characteristics and the second part consist of COVID-19 transmission as well as its survivability, precautions and psychological state during the outbreak. This was transferred to a Google form and the link was shared through social medias. Data were analysed using SPSS software v.23.0. Results: In spite of the fact that 88% of respondents worried about being infected with COVID-19 and well informed regarding fomite transmission, almost half of respondents (42.3%) did not sanitize their parcels received from outside. Conclusion: In light of this, health authorities should implement more campaigns to emphasize the utmost importance of disinfection of any foreign items by consumers and it is strongly believed that it will provide enhanced protection against fomite transmission.